2022
DOI: 10.21203/rs.3.rs-1392830/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Politics of COVID-19: Differences Between Blue, Purple, and Red States in COVID-19 Cases, Deaths, and Regulations

Abstract: Confining and controlling infectious diseases, currently COVID-19, is a challenging task for politicians around the world. Since not much has been known about the virus initially, political decisions had to be made under uncertainty. Thus, worldviews and beliefs of politicians heavily influenced political decisions. The current study investigated political decisions in 2020 and 2021 and their influence on COVID-19 deaths in the 50 states of the United States, with a particular focus on comparing red (Republica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Restrictions in red states were not as strict as in blue states. Guess et al ( 40 ) found that blue states had significantly higher scores than red states on behavioral/mitigation efforts. These include the duration of lockdowns, mask mandates, and vaccination rates.…”
Section: Discussionmentioning
confidence: 99%
“…Restrictions in red states were not as strict as in blue states. Guess et al ( 40 ) found that blue states had significantly higher scores than red states on behavioral/mitigation efforts. These include the duration of lockdowns, mask mandates, and vaccination rates.…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the political action and many of the governmental policies concerning vaccines have had a positive impact on responding to the Covid-19 pandemic, the challenges emerging with regard to vaccines have had a detrimental impact on the response to the pandemic. For example, in the United States, the public's reaction to government policies enacted to contain the pandemic with respect to vaccines has resulted in a polarization of the different states based upon political ideologies and parties (Clark 2021;Guess et al 2022). Specifically, in the United States, political conservatives are less credulous about the scientific rhetoric that vaccines are safe or even effective, which has resulted in what is called "red Covid" (Leonhardt 2021).…”
Section: Evidence-based Corona Medicinementioning
confidence: 99%